Geotechnical properties of kaolinite reinforced with straw paper cut fibers and straw paper pulp - İncircioğlu, Serdar. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
The objective of this research is to modify the fabric of clay by mixing it with paper fibers in different forms. Fiber addition to clay is not a common procedure; however finite length fibers of tire buffings, polypropylene fibers are investigated in the literature to improve the clay properties. This study investigates a different original approach in modification of clay fabric by mixing it with paper pulp fiber which acts as matrix fiber rather than individual fiber. Modified kaolinite clay samples were prepared at paper cut fiber inclusion ratios of 0.25%, 0.50%, and 1.00% by weight and at paper pulp inclusion ratio of 1.00% by weight. Direct shear tests, linear shrinkage tests, unconfined compression and splitting tensile tests and also hydraulic conductivity tests were conducted. These tests were also conducted on pure kaolinite to compare the effects of adding straw paper to kaolinite. Paper cut fibers improved shear strength, unconfined compressive strength, and splitting tensile strength. Paper pulp form improved workability, plasticity, and absorption of water. Hydraulic conductivity test results showed that addition of paper pulp and paper cut fibers to clay reduced hydraulic conductivity by one order of magnitude. Easy and fast application of straw paper in modification and reinforcement of kaolinite clay makes it a good candidate for soil improvement.
Keywords: Reinforced concrete, Fiber.; Kaolinite.